2007
DOI: 10.1111/j.1423-0410.2007.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐thaw viable CD34+ cell count is a valuable predictor of haematopoietic stem cell engraftment in autologous peripheral blood stem cell transplantation

Abstract: Quantification of post-thaw viable CD34(+) cells better represents the actual composition of the graft and may be a more accurate predictor of haematopoietic engraftment than post-thaw total CD34(+) cell counts, or prefreeze determinations, especially for platelet engraftment. It is necessary to develop good quality controls for freezing and thawing procedures to minimize variance in cell viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 18 publications
(21 reference statements)
3
56
0
1
Order By: Relevance
“…In addition, most DMSO depletion strategies will also concomitantly remove cell debris and reduce neutrophil, platelet and other blood cell-derived soluble mediators, which may further contribute to decreasing the adverse event incidence and severity (2). Indeed, many studies have suggested that DMSO depletion can reduce adverse reactions, with minimum effects or even improvements on engraftment after HSC transplantation (2,5,7,13,55,105,106). Given the lack of consensus, no specific requirements regarding removal of DMSO from HSC grafts prior to infusion have been issued by the regulatory agencies or accreditation associations, instead leaving the decision to the discretion of physicians and clinical institutions to set their own policies and guidelines.…”
Section: Physiological Role Of Dmso In Adverse Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most DMSO depletion strategies will also concomitantly remove cell debris and reduce neutrophil, platelet and other blood cell-derived soluble mediators, which may further contribute to decreasing the adverse event incidence and severity (2). Indeed, many studies have suggested that DMSO depletion can reduce adverse reactions, with minimum effects or even improvements on engraftment after HSC transplantation (2,5,7,13,55,105,106). Given the lack of consensus, no specific requirements regarding removal of DMSO from HSC grafts prior to infusion have been issued by the regulatory agencies or accreditation associations, instead leaving the decision to the discretion of physicians and clinical institutions to set their own policies and guidelines.…”
Section: Physiological Role Of Dmso In Adverse Reactionsmentioning
confidence: 99%
“…Many approaches have been applied to reduce the adverse effects of cryopreserved hematopoietic stem cell transplantation, such as: (1) systematic premedication before infusion (62), (2) hydration and allopurinol administration after infusion (62); (3) slowing down the infusion speed and prolonging the infusion time (2,62), (4) dividing the infusion into multiple aliquots given several hours or days apart (10,62); (5) further concentrating HSC grafts to reduce the cryopreservation volumes and corresponding DMSO content (2); (6) reducing % DMSO concentration for cryopreservation to lower than 10%, or use alternative CPA to mix with or replace DMSO (2,108110); and (7) removing DMSO before infusion (2,5,7,13,55,105,106). Since the side effects are idiosyncratic thus unpredictable so far to our knowledge, all these approaches are suggested to be combined to reduce the reaction incidence as low as possible.…”
Section: Reducing the Infusional Side Effects Of Cryopreserved Hsc Grmentioning
confidence: 99%
“…In some sensitive cell cultures, such as of embryonic stem cells, the presence of necrotic cells release factors that negatively impact the health of the entire culture in a cascading manner 2, 5 , therefore periodic removal of dead cells improves culture health. Also the presence of nonviable cells can be detrimental to clinical outcomes of cell therapies, for example the delaying of engraftment time of hematopoietic stem cell transplantation 68 . While the immune system of organisms can identify and remove dead and dying cells from the body, the presence of debris and dead cells in in vitro cell culture adversely affects its quality and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Before freezing, the total number of CD34+ cells is determined, and this number is used post-thaw to determine the total cell number administered to the patient. In a 2008 study by Lee et al [87], PBSCs were analyzed via flow cytometry of 7-AAD and CD34 after collection from 36 patients and immediately post-thaw. Thawed PBSCs were administered to patients and the time to engraftment was determined by daily blood counts.…”
Section: Preclinical Assays For Qualitymentioning
confidence: 99%